Commentary on the Current Status of Minimal Invasive Surgery - Tagarakis, Georgios I.; Geropoulos, Nikolaos; Voucharas, Christos; Tsolaki, Fani; Alexiou, Ioannis; Vouchara, Angeliki; Tagarakis, Ioannis (Archives of Clinical and Medical Case Reports, 2024)
Minimal invasive surgery has been continuously advancing during roughly the last three decades. Despite the cost of the related equipment and the often considerable learning curve, the advantages of a lesser perioperative pain and a of a better cosmetic result with comparable surgical- oncological outcomes have contributed to the dissemination of minimal invasive procedures in all surgical disciplines. The current commentary aims to highlight the basic points of comparison between open and minimal invasive surgery, focusing of the main advantages and disadvantages of each category.